Supporting pre-service teachers in developing research competence - Gussen, Lea; Schumacher, Fabian; Großmann, Nadine; Ferreira González, Laura; Schlüter, Kirsten; Großschedl, Jörg (Frontiers in Education, 2023)
Teachers need research competence to reflect on their teaching and to interpret and implement research-based recommendations. However, many pre-service teachers have critical attitudes toward research, little motivation to engage in research, and comparatively low knowledge of research methods and thereby consequently indicating a low research competence. Flexible online modules in university teaching could be a promising approach to address these issues. Online modules can potentially promote self-determined motivation, but should be sufficiently structured to support learners’ need for competence. We designed two learning environments with different types of structure: a non-restrictive structured environment and a restrictive structured environment. A total of N = 108 pre-service biology teachers were randomly assigned to the two learning environments. Contrary to our assumption, the restrictive type of structure of the learning environment did not lead to a higher perception of competence. This might be a consequence of external pressure, for example, the examination at the end of the course. Regarding pre-service teachers’ research competence, we found a decrease in the affective-motivational domain and an increase in the cognitive domain in both learning environments. These results suggest that fostering pre-service teachers’ research competence should focus on the affective-motivational domain. In order to positively affect this domain, care must be taken to ensure that structuring elements are not experienced as control and that given choices are meaningful to students.